Prospects for economic diversification in Arab economies considering globaleconomic transformations -study Prospective- (Numerus academy review, 2026)
This study aims to conceptualize the future diversification of Arabeconomies, , the study concluded that some Arab countries have made great strides towards diversifying their economies, and this is the allowance of the GulfCooperation Council, while the rest of the countries expect their dependence on a few sectors to remain unsustainable or uncompetitive due to continued politicalinstability.